In vitro activity of DU-6859a against anaerobic bacteria. - Wexler, H M (1994)
The activity of a new quinolone agent, DU-6859a, against 330 strains of anaerobic bacteria was determined by using the National Committee for Clinical Laboratory Standards-approved Wadsworth brucella laked blood agar method; the activity of DU-6859a was compared with those of amoxicillin-clavulanate (2:1), chloramphenicol, ciprofloxacin, clindamycin, fleroxacin, imipenem, lomefloxacin, metronidazole, sparfloxacin, and temafloxacin. DU-6859a and chloramphenicol inhibited all of the isolates at concentrations of 1 and 16 micrograms/ml, respectively; amoxicillin-clavulanate, imipenem, and metronidazole inhibited > or = 94% of the isolates at their respective breakpoints (8, 8, and 16 micrograms/ml). MICs of DU-6859a at which 90% of the strains were susceptible were 1 to 5 twofold dilutions lower than those of the other quinolones for every group of organisms. MICs of DU-6859a at which 90% of the strains were susceptible (total numbers of strains tested are in parentheses) were < or = 0.25 micrograms/ml for Bacteroides fragilis (57), other B. fragilis group species (84), Bilophila wadsworthia (15), Clostridium species (27) (including C. difficile, C. perfringens, and C. ramosum), Fusobacterium nucleatum (16), Fusobacterium mortiferum-F. varium group species (10), Peptostreptococcus species (20), non-spore-forming gram-positive rods (20), and Prevotella species (25).